High-Dose Tranexamic Acid Enhances Circulating Neutrophil Extracellular Traps and Thrombus in Thrombosis Mouse Model - Jung-Wook Song; Eun-Hye Seo; Un Yung Choi; Chung-Sik Oh; Aram Kim; Keeho Song; Seung-Hyun Lee; Jin Kook Kim (Biomedicines)
Background/Objectives: Tranexamic acid (TXA) reduces mortality in patients with massive hemorrhage by inhibiting fibrinolysis. However, it is associated with an increased risk of thrombosis. The activation of neutrophil extracellular traps (NETs) has been implicated in the formation of thrombosis. This study investigated the effects of tranexamic acid on circulating and localized NETs, neutrophils, platelets, and the vascular endothelium in a mouse model of thrombosis. Methods: A ferric chloride-induced thrombosis mouse model was used and divided into five groups: a Control group that received intraperitoneal phosphate-buffered saline (PBS), and four experimental groups that received intraperitoneal tranexamic acid at doses of 5 mg/kg, 10 mg/kg, 20 mg/kg, and 30 mg/kg, respectively. To evaluate the expression of circulating and localized NETs, neutrophils, platelets, vascular endothelial cells, fibrinogen, and D-dimer, the following markers were analyzed: myeloperoxidase (MPO), neutrophil marker, cluster of differentiation (CD)31, CD34, fibrinogen α-chain, and D-dimer. These markers were assessed using flow cytometry, immunohistofluorescence staining, and Western blot analysis. The primary endpoint was the differential expression of anti-MPO antibody among the groups. Results: In total, data from 20 thrombosis mouse models were analyzed. For each group, four samples were assessed by flow cytometry, and three samples by immunohistofluorescence staining and Western blot analysis, respectively. In the flow cytometric analysis, circulating anti-MPO antibody expression was significantly higher in the TXA 20 and TXA 30 groups compared to the Control group (p = 0.001 and p = 0.001, respectively). Immunohistofluorescence staining revealed that D-dimer expression in the thrombotic femoral artery was significantly lower in the TXA 5, TXA 10, and TXA 20 groups compared to the Control group (p = 0.005; p = 0.018; p = 0.004, respectively), but significantly higher in the TXA 30 group than in the Control group (p = 0.044). Similarly, the expression of anti-fibrinogen antibody was significantly lower in the TXA 5, TXA 10, and TXA 20 groups compared to the Control group (p = 0.038; p = 0.003; p = 0.041, respectively). Western blot analysis showed no significant differences in the expression of anti-Ly6B.2, anti-fibrinogen, and anti-CD31 antibodies among the groups. Conclusions: The present study suggests that high-dose tranexamic acid (30 mg/kg) administration may increase circulating NETs and localized D-dimer levels, indicating a higher potential for thrombosis in a thrombosis mouse model. These findings imply that the prothrombotic effects of tranexamic acid may be dose-dependent and could vary based on underlying disease conditions. Therefore, the careful dosage adjustment of tranexamic acid may be necessary, particularly in patients at risk of thrombosis.